Efficacy and safety of vasopressin and terlipressin in preterm neonates: a protocol for a systematic review. Issue 1 (9th June 2021) - Alsaadi, Abdulrahman Salim; Sushko, Katelyn; Bui, Vivian; Van Den Anker, John; Razak, Abdul; Samiee-Zafarghandy, Samira
Abstract : Background: The use of vasoactive agents like arginine vasopressin (AVP) and terlipressin to treat hypotension or persistent pulmonary hypertension in critically ill preterm neonates is increasing. Therefore, a systematic review of the available data on dosing, efficacy and safety of AVP and terlipressin in this patient population appears beneficial. Methods: We will conduct a systematic review of the available evidence on the use of AVP and terlipressin for the treatment of hypotension or persistent pulmonary hypertension in preterm neonates. We will search Ovid MEDLINE, EMBASE, the Cochrane Central Register of Controlled Trials, Web of Science and Google Scholar from inception to March 2021. Two reviewers will independently screen titles and abstracts, review the full text of eligible studies, extract data, assess the risk of bias and judge the certainty of the evidence. Our primary outcome will be an (1) improvement of end-organ perfusion after initiation of AVP or terlipressin and (2) mortality prior to discharge. Our secondary outcomes will include (1) major neurosensory abnormality and (2) the occurrence of adverse events. Discussion: The currently available evidence on the efficacy and safety of AVP and terlipressin in preterm neonates is limited. Yet, evidence on the pharmacology of these drugs and the pathophysiology of vasoplegic shock support the biological plausibility for their clinical effectiveness in this population. Therefore, we aim to address this gap concerning the use of vasopressin and terlipressin among critically ill preterm neonates. Trial registration: This protocol has been submitted for registration to the international database of prospectively registered systematic reviews (PROSPERO, awaiting registration number).